Rapid induction of B-cell lymphomas: insertional activation of c-myb by avian leukosis virus. - Kanter, M R (1988)
EU-8 is a recombinant avian leukosis virus (ALV) constructed in vitro, which carries long terminal repeats and gag and pol genes from ring-necked pheasant virus and the env gene from UR2AV. Unlike either parent virus, when injected into 10-day-old chicken embryos, EU-8 induces a high incidence of clonally arising B-cell lymphomas within an unusually short latent period, often causing death within 5 to 7 weeks after infection. These tumors differ from the classic lymphoid leukosis induced by ALV in several respects, both biologically and at the molecular level. Most notably, in all of the EU-8-induced tumors examined, the provirus was integrated in the c-myb locus, and in no tumors were c-myc integrations found. Most of the proviral integrations were downstream of the initiation codon of c-myb and thus presumably resulted in some truncation of the c-myb gene product, although not to the same extent as has been found in other cases of c-myb activation. In addition, several of the proviruses were integrated well upstream of the c-myb coding region. This is the first report of ALV interaction with the c-myb proto-oncogene and the first report of c-myb activation resulting in tumors of lymphoid rather than myeloid origin, suggesting that the target cell specificity of transformation by the myb gene is not as restricted as previously believed.